Law librarianship in the digital age - Kroski, Ellyssa (Lanham, Maryland The Scarecrow Press, Inc., 2014)
Law librarianship 2.0 / Jennifer Wertkin -- Embedded librarianship / Thomas J. Striepe and Mary Talley -- Copyright in the digital age / Kyle K. Courtney -- Open access to legal scholarship / Cheryl Kelly Fischer and Vicki Steiner -- User services analysis for decision making / Kim Clarke -- Law library management / Camille Broussard, Ralph Monaco, and Gitelle Seer -- Digitization / Michelle M. Wu -- E-books in law libraries / Ellyssa Kroski -- Tablets and mobile device management / William R. Mills -- The law library website / Andrew Plumb-Larrick -- Web-scale discovery and federated search / Valeri Craigle -- The cloud / Roger Vicarius Skalbeck -- Social software / Marcia L. Dority Baker -- Reference services in a law library / Carol A. Watson -- Introduction to legal research / Rhea Ballard-Thrower -- Online information sources / Sarah K.C. Mauldin -- Major legal databases and how to search them / Theodora Belniak -- Library instruction in the information age / Emily Janoski-Haehlen -- Educational technologies / Kim Clarke and Nadine R. Hoffman -- Technical services 2.0 / Edward T. Hart -- Collection development / Molly (Mary) E. Brownfield -- Electronic resources management and user authentication / Catherine M. Monte -- Knowledge management / Steven A. Lastres and Don MacLeod -- The law library intranet / Emily R. Florio and Michael J. Robak -- Digital age marketing / Carol Ottolenghi -- Competitive intelligence / Jennifer Alexander and M.T. Hennessey -- Getting the most from major associations, publications, and conferences / Holly M. Riccio -- The future of law librarianship / Scott D. Bailey and Julie Graves Krishnaswami
Includes bibliographical references and index.
Keywords: Law libraries -- Handbooks, manuals, etc; Libraries and the Internet; Digital communications -- United States